Influence of alcohol abuse and / or HIV infection on morpho-functional condition of the uterine tube in women of reproductive age - Lytvynenko, Marianna (ScienceRise: Medical Science, 2022)
The fallopian tubes are a key link in the relationship between the uterus and the ovary. The aim of our study was to determine the effect of alcohol abuse and / or HIV infection on the morpho-functional state of the fallopian tubes in women of reproductive age. Material and methods. The study included sectional material, which was selected from 100 women of reproductive age (20 to 40 years), who were divided into four groups. The first group included section material from 25 women who had been laboratory confirmed for HIV. The second group included sectional material selected from 25 women suffering from chronic alcoholism. The third group consisted of sectional material from HIV-positive women who also showed signs of alcohol abuse. The fourth group includes sectional material selected from HIV-negative women. Results. Gross pathological changes in the structure of the fallopian tube, due to both the impact of HIV infection and alcohol abuse was identified in each of the groups. Changes in morphometric parameters (length of the ampullary part, outer diameter of the tube at the junction of the isthmus in the ampullary part, the area of the lumen of the ampullary part) can cause severe complications of inflammation or lead to ectopic pregnancy. The study of the epithelial and muscular layer revealed destructive-sclerotic changes, which consist in reducing the height of the epithelium and increasing the proportion of connective tissue in the muscular layer of the tube. Conclusions. According to the study, HIV and alcohol abuse are diseases that affect all elements of the fallopian tube. Thus, HIV infection and chronic alcohol abuse can exacerbate each other's negative effects on the female reproductive system and cause morphometric changes that can form a substrate for the development of inflammatory processes and lead to ectopic pregnancy